Advanced magnetic resonance spectroscopy and imaging techniques applied to brain development and animal models of perinatal injury. Issue 45 (26th March 2015) - van de Looij, Yohan; Dean, Justin M.; Gunn, Alistair J.; Hüppi, Petra S.; Sizonenko, Stéphane V.
Abstract: Magnetic resonance spectroscopy (MRS) and magnetic resonance imaging (MRI) are widely used in the field of brain development and perinatal brain injury. Due to technical progress the magnetic field strength (B0 ) of MR systems has continuously increased, favoring 1 H‐MRS with quantification of up to 18 metabolites in the brain and short echo time (TE) MRI sequences including phase and susceptibility imaging. For longer TE techniques including diffusion imaging modalities, the benefits of higher B0 have not been clearly established. Nevertheless, progress has also been made in new advanced diffusion models that have been developed to enhance the accuracy and specificity of the derived diffusion parameters. In this review, we will describe the latest developments in MRS and MRI techniques, including high‐field 1 H‐MRS, phase and susceptibility imaging, and diffusion imaging, and discuss their application in the study of cerebral development and perinatal brain injury.